Developing a multi-level governance framework for sustainable forest landscapes: the prospects for REDD-plus - Fosci, Mattia (2014)
This dissertation is a grounded theoretical analysis of the REDD-plus programme, the multi-level system of forest governance that is being developed since 2007 under the international legal regime on climate change. It examines REDD-plus’ main elements, seeks to preliminarily assess its likely impact and suggests measures to improve its design. The focus is on effectiveness, intended as the ability to address the causes of forest loss in developing countries. The research is divided in two parts. The first part concentrates on REDD-plus at the international level. It explores the programme’s innovative but still fragmented and contradictory use of ‘policy approaches’ and ‘positive incentives’, and assesses its strengths and weaknesses in the context of the broader trend towards the ‘neo-liberalisation’ of international environmental policy. The second part examines REDD-plus at the national and sub-national levels. It uses sustainable landscape governance as the overarching conceptual and physical framework for the effective implementation of REDD-plus activities and suggests three areas of public policy that should be prioritised by participant countries: tenure, spatial planning and financial intermediation. The dissertation examines each policy area in detail and provides specific recommendations on the measures available to overcome current problems. It argues that the programme’s effectiveness would be magnified by combining public policy and market instruments in such a way as to facilitate the negotiation of trade-offs between multiple environmental and development objectives and between diverse stakeholders. Building on this analysis, the conclusions advance some considerations on the possible significance of REDD-plus for the development of international environmental law.